Determining genetic variants in children and adolescents suffering from tetralogy of Fallot with a positive family history: methodology: frequency of gene mutations in children and adolescents suffer from tetralogy of Fallot - Sabri, Mohammad Reza; Gharipour, Mojgan; Tayebi, Naeimeh; Sadeghian, Ladan; Javanmard, Shaghayegh Haghjooy; Sarrafzadegan, Nizal (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Congenital heart disease (CHD) affects near 1% of all live births and is considered to be the main reason of morbidity and mortality in early childhood. In this study, we investigated molecular genetics factors associated with Tetralogy of Fallot (TOF) using high throughput technologies in the consanguineous families with at least 2 affected individual. Method: This family study started in March 2017 to May 2018 in pediatric cardiovascular research center, Cardiovascular Research Institute, Isfahan, Iran. After obtaining informed consent, we invited families who had at least 2 individuals in one generation or previous generations with familial marriage history and they were included in the study. Genomic DNA was extracted from peripheral blood lymphocytes of the patient and samples were investigated for structural variations such as deletion or duplication in the genome using single nucleotide polymorphism array (SNP array). In the next step, if the SNP array is negative, next generation study will be performed in the propend and after analyzing the raw data and filtering for rare pathogenic variants. Results: In this study, totally 5 families were evaluated. All affected and unaffected individuals of each family included in the pedigree. This study comprised 14 subjects (9 males and 5 females; 8.92 ± 6.21 years old). Baseline characteristics and clinical data of the study subjects are presented in Table 1. The prevalence of consanguineous marriage is 92.2% among parents, 71.4% among mother grandparents and 28.6% among father grandparents. 64.3 % of our participants have sibling with similar disease. The prevalence of atrial septal defect (ASD), ventricular septal defect (VSD), and arrhythmia and TOF was 7.1%. Conclusion: We found some families with 2 or more CHD and with a high rate of consanguineous marriage and probably suffering from a genetic predisposition. We aim to exam them further with next generation study (NGS) to find any genetic defect and then to exam other CHD’s in our region. Key words: gene mutations, children, adolescents, tetralogy of Fallot, family history.